THE EFFECT OF MIND MAPPING TECHNIQUE ON STUDENTS’ ACHIEVEMENTIN WRITING ANALYTICAL EXPOSITION TEXT - Eka Widya Astuti; Ashari P. Swondo (Journal MELT (Medium for English Language Teaching), 2021)
The completion of this comparison aims to determine the effect of increasing student achievement in writing analytical exposition texts using the Mind Mapping technique and without the Mind Mapping technique. This comparative research is a qualitative research, which involves high school grade 3 students as the population of this comparison, these students who are students from Creativkids Medan. The result of this comparison is that the value of 67.53 is the value obtained using the Mind Mapping technique. Another thing that does not use the Mind Mapping technique gets a score of 63.5. This also causes if students who use the Mind Mapping technique get the t_obs of 3.43 points, which means that it increases more than t table 2.00. This has the effect that the alternative hypothesis (Ha) has been accepted and the null hypothesis (Ho) has been rejected. And this makes the reason for the increase in student achievement figures by using the Mind Mapping technique to write analytical analysis texts. So, it can be summarized that the Mind Mapping technique is very effective, appropriate, and easy to be applied by students who will create correct and directed analytical exposition text.